Association between interleukin-6 polymorphism in the-174 G/C region and hearing loss in the elderly with a history of occupational noise exposure - Braga, Miula Portelinha; Maciel, Sandra Mara; Moraes Marchiori, Luciana Lozza de; Poli-Frederico, Regina Celia [UNESP] (Assoc Brasileira Otorrinolaringologia & Cirurgia Cervicofacial, 2014)
Introduction: The biological processes involved in noise-induced hearing loss (NIHL) are still unclear. The involvement of inflammation in this condition has been suggested.Objective: To investigate the association between interleukin - 6 (IL-6) polymorphism and susceptibility to NIHL.Methods: This was a cross-sectional study with a sample of 191 independent elderly individuals aged >60 years of age. Information on exposure to occupational noise was obtained by interviews. Audiological evaluation was performed using pure tone audiometry and genotyped through PCR by restriction fragment length polymorphism - PCR-RFLP. Data were analyzed using the chi-square test and the odds ratio (OR), with the significance level set at 5%.Results: Among elderly with hearing loss (78.0%), 18.8% had a history of exposure to occupational noise. There was a statistically significant association between the genotype frequencies of the IL-6 - 174 and NIHL. The elderly with the CC genotype were less likely to have hearing loss due to occupational noise exposure when compared to those carrying the GG genotype (OR = 0.0124; 95% CI 0.0023-0.0671; p<0.001).Conclusion: This study suggests there is an association of polymorphisms in the IL-6 gene at position - G174C with susceptibility to noise-induced hearing loss. (C) 2014 Associacao Brasileira de Otorrinolaringologia e Cirurgia Cervico-Facial. Published by Elsevier Editora Ltda. All rights reserved.
Keywords: Occupational noise; Sensorineural hearing loss; Cytokines